Business process reengineering: a process based management tool - Bhaskar, Hari Lal (Serbian Journal of Management, 2018)
Purpose – Business systems are made up of processes. Processes are collection of activities of businesses that results in an output. And when processes become old and inefficient and can’t deliver results they must be redesigned or replaced. Business process reengineering is a tool for transformation of business process and unconstrained reshaping of all business processes. This study uses case and critical literature analysis (CLA) to investigate and focus on the development of business process reengineering (BPR) application concept and its outcome to the industrial set-up (service giving and manufacturing).Approach/methodology – The goal is achieved by case and critical literature analysis (CLA). The case validates its result and justifies its practicality. This study contributed in the context of BPR as a process based management tool for selecting, managing and reengineering selected processes for overall manufacturing or service quality improvement.Findings – In this study, a series of manufacturing processes and a framework for the guidelines of modeling has shown. Core processes of different industries has presented in effective manner. These validates that business process reengineering is a process-based management tool that can deliver both, either redesign or replace inefficient processes, as required, with a breakthrough result. It can be applied to single, group or entire processes comprising the organization.Practical implications – On the basis of presented case study & process modeling guidelines the managers can use BPR to redesign their inefficient processes.Originality/value – This approach suggests adopting BPR at any cost as a tool to improve all business processes as well as overall productivity and performance by managing their whole process. Case study motivates practitioners/managers towards reengineer and manages their business process.
Keywords: reengineering; BPR application; Inefficiency; tools; process; manufacturing; Bpr; business process; Business Process Reengineering